Eksplorasi Kurva Kuznets: Determinan Emisi CO2 dalam Pembangunan Ekonomi Kawasan ASEAN Periode 2014-2023 - Antari, Rochmat Bagus; Ratnasari, Emma Dwi; Islami, Fitrah Sari (Economie: Jurnal Ilmu Ekonomi, 2025)
Global warming is very serious because for the first time the average annual temperature has crossed the threshold of 1.5 ° C. One of the causes of the increase in temperature is the presence of greenhouse gases (GHG) and carbon dioxide (CO2) is one of these gases. ASEAN is a regional organization whose member countries are mostly middle income countries and also has high economic growth because they are in the stage of economic development where according to the environmental kuznet curve (EKC) hypothesis this will increase environmental degradation. In addition, ASEAN has a high level of CO2 emissions. This study aims to analyze the factors that influence carbon dioxide emissions in ASEAN from 2014 to 2023. The variables used are CO2 emissions as the dependent variable, then GDP, FDI, Population, and Industrial Rate as the dependent variables, then analyzed using the panel data regression method. The results of the study showed that GDP and Population have a significant positive effect on CO2 emissions while FDI and Industrial Rate produce negative coefficients but do not have a significant effect on CO2 emissions.